Transparansi dan Akuntabilitas dalam Pengadaan Publik: Meningkatkan Integritas dan Efisiensi - Supawanhar, Supawanhar; Romdana, Romdana; Pratama, Raka Agusta; Purnamasari, Melani (SENGKUNI Journal (Social Science and Humanities Studies), 2022)
Transparency and accountability play a key role in successful public procurement. This article discusses how increased transparency in the procurement process can lead to higher levels of integrity, while simultaneously improving the efficiency of public resource management. Through a more open and measured approach, governments can minimize the risk of abuse of power, corruption, and wasteful spending, while also strengthening public trust in public institutions. This article highlights the importance of concrete steps to achieve this goal and provides insights into how increased transparency and accountability can be key to success in more dignified and efficient public procurement.